Sustainability and Energy Efficiency in Fluid Power - Recent Advancements in Research and Industry - Schmitz, Katharina (International Conference Fluid Power 2025: Conference Proceedings, 2025)
Sustainability in all its three dimensions is a major driver for recent advancements in many sectors. In fluid power applications, sustainability and decarbonization are often linked to energy efficiency and reducing energy losses. Therefore, different new approaches and examples exist in research and in industry. Digital tools enable new advancements and additional methodology for developments. The paper gives an example of recent advancements and discusses the need for further developments in research and industrial development.